2009
DOI: 10.1111/j.1748-5967.2008.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weather factors on populations of Helicoverpa armigera moths at cotton‐based agro‐ecological sites

Abstract: Pheromone trapping was used to monitor populations of the moth Helicoverpa armigera at five cotton‐based agro‐ecological sites – river, vegetable, orchard, forest and clean cultivation (areas under only cotton cultivation) – in the Bahawalpur district, Pakistan. Three locations at each site were chosen and three pheromone traps at each location were installed in cotton fields. Moth catches were recorded at 15–20 day intervals from 24 October 2004 to 19 December 2006. In 2004, the river sites showed the maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…(1991) also found that the mean temperature had a positive correlation with the population density of H. armigera . In the case of cotton, the population fluctuation of bollworm was also influenced by the maximum temperature and relative humidity but minimum and average temperatures had no influence (Aheer et al . 2009; Khan et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1991) also found that the mean temperature had a positive correlation with the population density of H. armigera . In the case of cotton, the population fluctuation of bollworm was also influenced by the maximum temperature and relative humidity but minimum and average temperatures had no influence (Aheer et al . 2009; Khan et al .…”
Section: Resultsmentioning
confidence: 99%
“…Mehto et al (1985) and Yadava et al (1991) also found that the mean temperature had a positive correlation with the population density of H. armigera. In the case of cotton, the population fluctuation of bollworm was also influenced by the maximum temperature and relative humidity but minimum and average temperatures had no influence (Aheer et al 2009;Khan et al 2009). Similarly, Han (2000) found that the mild temperature was positively correlated; however, minimum temperature was negatively correlated with the infestation of H. armigera.…”
Section: Relationship Of H Armigera Larvae With Weather Factorsmentioning
confidence: 99%
“…Incidence of these species was observed in order R. padi>S. graminum>S. avenae. period Aheer et al [30] found that aphid population decreased when maximum and minimum temperatures reached their optimum limits of 27.30°C and 24°C, respectively. Our findings are also support the above statement, as aphid populations are minimum at the beginning of February (temperature <16C 0 ) and the end of March (temperature > 27C 0 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, this may have resulted from several factors, including the inherent properties of a species population in relation to environmental conditions [ 46 , 47 ]. Warmer temperatures and increased precipitation, for instance, can reduce the rates of population growth [ 48 ]. Additionally, because there is no similar analysis in the literature, some of the answers are difficult to translate from a strictly agro-ecological perspective.…”
Section: Resultsmentioning
confidence: 99%